Creation Out of Nothing. Fascist Propaganda in Litzmannstadt - Ostrowski, Marek (Following Rhetoric, Stylistics and Journalism. A Volume Dedicated to Professor Barbara Bogołębska, 2019)
The article discusses activities of the Nazi propaganda in Litzmannstadt (Nazi name for Lodz, Poland). Said propaganda promoted central concepts of fascist ideology such as Volk, land and leadership in battle. The goal of political and military action was to restore and maintain the cultural domination over other nations. The Nazi state was ethnically, linguistically and racially uniform – it lacked the concept of tolerance towards ethnic minorities. An important feature of this propaganda was its impact on the activities of administrative organs.